Extracavitary primary effusion lymphoma: A case report from India - Rajalakshmi Sampath; Marie Therese Manipadam; Sheila Nair; Inian Samarasam (Wolters Kluwer Medknow Publications, 2015)
We present a case of extracavitary primary effusion lymphoma presenting, as jejunal polyps in a 38-year-old man. This is the first report of this entity from India. Although rare in our country, the diagnosis should be suspected in cases of CD20 negative large cell lymphoma with plasmablastic or immunoblastic differentiation in seropositive patients. Immunostaining for latency-associated nuclear antigen-1 and in situ hybridization for Epstein-Barr virus-associated RNA will confirm the diagnosis.